1978
DOI: 10.1007/bf01922922
|View full text |Cite
|
Sign up to set email alerts
|

‘Boost’ in gibberellin response by water-stress in seedling growth

Abstract: The seedling growth of Brassica campestris var. varuna, has been studied, as affected by water-stress and gibberellin treatments. A 'boost' in the net GA response due to water-stress, has been observed. Thus presence of GA can overcome the water-stress effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Several studies, for example, have indicated that endogenous GA levels are sensitive to excesses or deficiencies in soil moisture (Rood et al , 2000; Dat et al , 2004; Steffens et al ., 2006). Moreover, exogenous GA application has been shown to increase growth under flooded (Rijnders et al , 1997; Dat et al , 2004) and drought (Rai et al , 1978, Pandey et al , 2004) conditions. Paclobutrazol, on the other hand, often further suppresses growth under water stress (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, for example, have indicated that endogenous GA levels are sensitive to excesses or deficiencies in soil moisture (Rood et al , 2000; Dat et al , 2004; Steffens et al ., 2006). Moreover, exogenous GA application has been shown to increase growth under flooded (Rijnders et al , 1997; Dat et al , 2004) and drought (Rai et al , 1978, Pandey et al , 2004) conditions. Paclobutrazol, on the other hand, often further suppresses growth under water stress (e.g.…”
Section: Introductionmentioning
confidence: 99%